Exploring Educational Media on Indonesian Studies for Third-Culture Kids’ Identity Development - Hefira, Vania (Universitas Multimedia Nusantara, 2024)
Indonesian Generation Z faces challenge in strengthening their national identity because of globalization. This is an urgency as Indonesia is progressing towards “Golden Indonesia 2045” where the goal is to have an advanced cultural richness over shared identity. One segmentation of Generation Z that encounters a challenge in self-identity perception is Third-Culture Kids (TCK). Their disconnection from the national identity during identity development can trigger identity crisis. One way to nurture their national identity is through teaching them Indonesian studies, consists of Indonesia’s cultural heritage, history, tradition, core values, and language. However, many TCKs struggle as they have short attention spans and language barriers towards most conventional educational media delivered in Indonesian language. This paper aims to fill in the gap of the limited research on this topic. The method is through qualitative method by reviewing previous studies on educational media related to Indonesian studies. This goal is to provide recommendations for further education development, in providing educational media for TCKs. The results underline the importance of interactivity aspects and the use of bilingual language, which has significantly helped BIPA students. The results suggest implication to design an interactive educational media that supports TCKs’ learning characteristics with local community involvement. The school managerial implication is to provide educators with inclusive education trainings and support families with transition programs during school induction. Keywords: third-culture kids; Indonesian studies; educational media; interactivity, golden Indonesia 2045